Podcast learning media: content on social science subjects for junior high school in grade VIII - Vitri Yanti,; Alwen Bentri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The use of podcast learning media in the Social Studies subject at Al-Azhar 32 Junior High School in Padang City is an essential innovation in enriching learning resources that support the development of students. This podcast allows students to learn independently at home or school. The research and development of this podcast aim to produce high-quality materials through evaluations from material validators, media validators, and students. The research method used is Research and Development (R&D). Assessments from three material validators, two media validators, and one material validator show that the presented material is valid, with a score of 4.8. Meanwhile, in terms of media aspects, the obtained scores are 4.0 and 4.5, indicating a high level of validity. The trial was conducted on 25 eighth-grade students at Al-Azhar 32 Junior High School in Padang City during the second semester of the 2022/2023 academic year. The trial results show that this podcast product is efficient, with an average score of 4.5. Therefore, the podcast is ready to be developed and can be used practically in the learning process, both in the classroom and independently. This podcast material can be accessed online through the YouTube channel and downloaded for offline access.